Electro osmotic pulsing technology (PLEOT) – a new potential solution for protection of cultural heritage - Treu, A. (2010)
Wood protection and control of infestation in buildings and other wooden cultural heritage objects is mainly based on chemical-, gas- and heat treatments. Degradation of wood is not only caused by fungi or bacteria but also by insects. Termites have been a potential risk to wooden structures not only in the warmer regions of our continents but also beyond the regions of their natural habitat due to transport of wood. A new environmental friendly wood protection system has been tested on wood destroying fungi and termites. Wood protection by means of electro osmotic pulsing technology (PLEOT) can preserve wood in service without using any chemical protection at all. The system can easily be installed and is very low in maintenance costs. The results show no mass loss of PLEOT protected beech and Scots pine sapwood samples exposed to the white rot Trametes versicolor for 4 and 8 weeks. Termite attack could slightly be reduced by using this technology on Scots pine sapwood samples.